2018
DOI: 10.5430/ijfr.v9n2p191
|View full text |Cite
|
Sign up to set email alerts
|

Value and Size Effects in the Stock Market of the Philippines

Abstract: Several market abnormalities, such as the small size effect or the value effect, have been found in the stock markets across the world. In this article it is analyzed the case of the stock market of the Philippines. The Philippines, while having a relatively large economy and a capital market with long history, has attracted less research than other Asian countries, such as China or Japan. This is perhaps due to the much larger size of the economies and capital markets of those countries. Nevertheless the stoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For instance, a systematic literature review focused on studies from the period 2007-2017 showed a partial reconciliation of the results of the research taken into account with the conclusions of value investing proponents, while the growth investing was not supported (Battisti et al, 2019). On the other hand, according, inter alia, to Perez (2018) and Hedau (2020), value investing did not lead to the outperformance of growth investing. Such heterogeneity confirms the purposefulness of research in this field.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, a systematic literature review focused on studies from the period 2007-2017 showed a partial reconciliation of the results of the research taken into account with the conclusions of value investing proponents, while the growth investing was not supported (Battisti et al, 2019). On the other hand, according, inter alia, to Perez (2018) and Hedau (2020), value investing did not lead to the outperformance of growth investing. Such heterogeneity confirms the purposefulness of research in this field.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By contrast, other researchers have found that the value/growth anomaly is not captured in every market. Two recent studies comparing Value stock performance against that of Growth stock have been carried out by Gerry and Perez (2018a;2018b). The first one (2018a) focusing on the South Korean stock market has been based on the period 1996-2016.…”
Section: Anomalies Considerationsmentioning
confidence: 99%